Influence of high levels of B-vitamins on starter pig performance - Kats, L.J.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 318 pigs was used in a 25-d growth trial to determine the influence of high levels of B-vitamins on starter pig performance. At weaning (l6-d of age), pigs were blocked by weight to one of six dietary treatments based on B-vitamin level. The negative control diet contained the standard KSU B-vitamin additions. The next four diets contained vitamin B12, riboflavin, pantothenic acid, or niacin at lOx the level recommended by NRC (1988). The positive control diet contained all four vitamins at 10 x the levels suggested by NRC (1988). B-vitamin inclusion rate did not influence average daily gain or feed intake. High levels of riboflavin resulted in a slight improvement in feed efficiency compared to pigs fed the control diets. These results do not support including B-vitamins in the starter diet at levels higher than currently recommended by KSU.
Keywords: Swine; Starter; Performance; B-vitamins